Pengaruh kemiskinan terhadap indeks pembangunan manusia (ipm) di provinsi sumatera selatan tahun 2016-2020 - Trisno, Tahan Upoyo; Munajat; Oktarina, Yetty (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of poverty (x), on the human development index (y)in South Sumatra in 2016-2020. The data used is secondary data from the CentralStatistics Agency. The analytical method used is panel data regression. The results of thet test show that poverty (x) has a negative and significant effect on the human developmentindex (y). The results of the coefficient of determination test show that the dependentvariable can be explained by the independent variable by 12.03% and the remaining87.97% is explained by other factors outside this model